The Role of K.H Muhammad Burkan Saleh in The Development of Islam in Kerinci - Satria, Oga (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
The process of Islamic development in each region was heavily influenced by scholars from outside the region and local residents within the area. As time goes by, the role of the clergy in the process of Islamic development becomes increasingly important because it is accompanied by various problems and needs of the people they face. Therefore, it is important to confirm their contribution from time to time as K.H Muhammad Berkan Saleh has done. This survey uses a qualitative research method. While the approach used in this study is historical in nature which allows us to see the events that surrounded K.H Muhammad Berkan Saleh throughout his lifetime. In addition, this study uses a philological approach to the works written by K.H Muhammad Berkan Saleh. Proses perkembangan Islam di setiap daerah banyak dipengaruhi oleh para ulama baik dari luar daerah maupun penduduk lokal di dalam daerah tersebut. Seiring berjalannya waktu, peran ulama dalam proses pembangunan Islam menjadi semakin penting karena dibarengi dengan berbagai masalah dan kebutuhan umat yang dihadapinya. Oleh karena itu, penting untuk mengkonfirmasi kontribusi mereka dari waktu ke waktu sebagaimana yang dilakukan oleh K.H Muhammad Berkan Saleh. Survei ini menggunakan metode survei kualitatif. Sedangkan pendekatan yang digunakan dalam penelitian ini bersifat historis yang memungkinkan kita untuk melihat peristiwa-peristiwa yang melingkupi K.H. Muhammad Berkan Saleh semasa hidupnya. Selain itu, penelitian ini menggunakan pendekatan filologi terhadap karya-karya yang ditulis oleh K.H. Muhammad Berkan Saleh.